What determines executives’ remuneration in Malaysian public listed companies? - Maziar Ghasemi; Nazrul Hisyam Ab Razak (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper examines the impact of executives’ ownership, firm profitability, board size and its components, as well as some other financial factors, on executives’ remuneration in the context of Malaysia. Using a sample of 2403 firm-years during 2006-2014 among listed companies in Bursa Malaysia, the findings show that firm profitability, leverage and number of non-executive directors have negative effects on executives’ remuneration. Conversely, dividends, percentage of executives’ directors, board size and size of firms have positive effects on executives’ remuneration. There is no evidence that executives’ ownership has significant effects on their remuneration. From the viewpoint of the agency theory about the effects of larger boards, firm profitability, and executive percentage on executives’ remuneration, it is perceived that the weak governance exists among listed companies in the Malaysian market. The insignificant impact of executives’ ownership on their remuneration is an important finding of this research.